Contacts to semiconductors fundamentals and technology - Brillson, L. J. (Materials science and process technology series. Electronic materials and process technology., 1993)
This book bridges the macroscopic, mesoscopic, and atomic-scale regimes of contacts to semiconductors. It discusses growing, processing, and characterizing electronic junctions. It includes descriptions of a wide array of techniques ranging from advanced ohmic, Schottky, and heterojunction contacts to microscopic junctions gleaned from ultrahigh vacuum surface science techniques.